NŪR MUḤAMMAD IN THE PERSPECTIVE OF THE TIJANIYAH TAREKAT - Nur Hadi Ihsan; Muhammad Thoriqul Islam (Sekolah Tinggi Agama Islam Sadra, 2023)
Nūr Muḥammad is one of the teachings in Sufism that studies the beginning of the creation of the universe. The Sufis discussed Nūr Muḥammad through God's tajallī (manifestation), and they believed that only Insan Kamil (Perfect Humans) possessed the perfection of His tajallī. This Sufi theory can be comprehended through the dhawqi approach. This research will deal with Nūr Muḥammad's theory of Sufism through the perspective of Tijaniyah Tarekat. The data for this study was obtained through library research utilizing a documentary technique. The collected data will be analyzed using the descriptive analysis method. This study finds that the Tijaniyah Tarekat is a Sufism institution that bases its teachings and practices on the concept of Nūr Muḥammad in the form of ṣalawāt al-fātiḥ and ṣalawāt jawharah al-kamāl. This Tarekat's elucidation of Nūr Muḥammad is also built on and consistent with the explication of authoritative Sufis in Islam's intellectual and spiritual tradition.